Prehypertension, hypertension, and the risk of acute myocardial infarction in HIV-infected and -uninfected veterans. - Armah, Kaku A; Chang, Chung-Chou H; Baker, Jason V; Ramachandran, Vasan S; Budoff, Matthew J; Crane, Heidi M; Gibert, Cynthia L; Goetz, Matthew B; Leaf, David A; McGinnis, Kathleen A; Oursler, Krisann K; Rimland, David; et al. (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2014)
Compared to uninfected people, human immunodeficiency virus (HIV)-infected individuals may have an increased risk of acute myocardial infarction (AMI). Currently, HIV-infected people are treated to the same blood pressure (BP) goals (<140/90 or <130/80 mm Hg) as their uninfected counterparts. Whether HIV-infected people with elevated BP have excess AMI risk compared to uninfected people is not known. This study examines whether the association between elevated BP and AMI risk differs by HIV status.
Keywords: Cohort Studies; Female; HIV Infections; Humans; Hypertension; Longitudinal Studies; Male; Middle Aged; Myocardial Infarction; Prehypertension; Prospective Studies; Risk Assessment; Veterans